Simple-sum versus Divisia monetary aggregates for Malaysia: cointegration, error-correction model and exogeneity - Habibullah, Muzafar Shah; Mohamed, Azali; Baharumshah, Ahmad Zubaidi (Universiti Putra Malaysia Press, 2000)
In this study we attempt to investigate the long run relationship between money and income in Malaysia. We constructed Divisia monetary aggregates for Malaysia and compared its performance with the Simple-sum monetary aggregates for the period 1980:1 to 1994:4. The long run relationship between the monetary aggregates and income were evaluated using the Engle-Granger's two-step procedure (testing for cointegration) and the error-correction for weak exogeneity-and superexogeneity. Our result suggest that the use of monetary aggregates as policy indicators are not subject to the Lucas critique and that there is potential role for Divisia monetary aggregates as a useful guide for monetary policy purpose in Malaysia.